Umteteli wa Bantu and the constitution of social publics in the 1920s and 1930s. (2nd January 2019) - Erlank, Natasha
ABSTRACT: Umteteli wa Bantu, launched in 1920, was much more than the moderate, black newspaper most of its contemporaries assumed it to be. Established by the Native Recruitment Corporation as an exercise in "soft power" through propaganda, the split created between its business and editorial functions facilitated editorial autonomy. Umteteli form, a term taken from Kevin Barnhurst and John Nerone's work on newspaper history, included the casual and irregular intermingling of social and personal news with all the other paper content. By sewing people and their activities into the fabric of the paper, Umteteli created a niche and identity for itself as constitutive of black sociality in which the constraints imposed by racial segregation no longer impeded upward social mobility. This playfulness and creativity contradict much of what is written about the paper, usually assessed for whether its political content was supportive or not of African nationalism. Also, through ongoing encouragement and exhortation to its readers, the paper drew readers into a status as co-producers, creating commonality through the relationship of readers to the paper where that commonality might not have existed otherwise.